Ligand‐free Palladium‐Catalyzed Carbonylative Suzuki Coupling of Aryl Iodides in Aqueous CH3CN with Sub‐stoichiometric Amount of Mo(CO)6 as CO Source. Issue 9 (22nd March 2019) - Sun, Nan; Sun, Qingxia; Zhao, Wei; Jin, Liqun; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan
Abstract: A new method for the synthesis of diaryl and heterodiaryl ketones has been established based on the palladium‐catalyzed carbonylative Suzuki coupling approach with sub‐stoichiometric Mo(CO)6 as CO source. Using 0.5 mol% of Pd(TFA)2 as catalyst, 0.5 equivalent of Mo(CO)6 as solid carbonyl reagent and 3 equivalent of K3 PO4 as base, a wide range of functionalized (hetero)aryl iodides and (hetero)aryl boronic acids could smoothly proceed the carbonylative cross‐coupling reaction in aqueous CH3 CN at 50 °C, affording the corresponding ketones in good to excellent yields. The newly developed method was easy to operate under mild conditions with high efficiency. Abstract :